Compactness of Fuzzy Cone Metric Spaces - Fadhel, Fadhel S; Abdullah, Amer A (Al-Nahrain Journal of Science, 2018)
Cone metric spaces may be considered as a generalization of determinist metric spaces or fuzzy metric spaces. In this paper, we will construct fuzzy cone metric space using different approaches, which is based on the definition of fuzzy points, and then study different types of compact subsets of such spaces, as well as, the relationship among them.